Peningkatan Kesadaran Ibu Hamil Terhadap Kunjungan Antenatal Care Melalui Penyuluhan - Hamdiah Anas; Nurlaeli Nurlaeli; Dewi Parwati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Antenatal Care (ANC) is a vital health service for pregnant women to monitor their pregnancy and detect complications early. However, some pregnant women still do not attend regular ANC visits due to low awareness and understanding of the importance of prenatal care. This community service activity aims to increase pregnant women's awareness of the importance of ANC visits through health education. Implementation methods included education, interactive discussions, and evaluation of participant understanding. The results of the activity indicate an increase in pregnant women's awareness and understanding of the benefits, schedule, and purpose of ANC visits. This activity is expected to encourage pregnant women to be more compliant in attending regular ANC visits to support the health of both mother and fetus.